Medulloblastoma: Challenges and advances in treatment and research. Issue 3 (18th November 2018) - Martirosian, Vahan; Neman, Josh
Abstract: Background: Medulloblastoma (MB) is a pediatric brain tumor occurring in the posterior fossa. MB is a highly heterogeneous tumor, which can be grouped into four main subgroups: WNT, SHH, Group 3, and Group 4. Each subgroup is different both in its implicated pathways and pathology, as well as how they are treated in the clinic. Recent Findings: Standard protocol for MB treatment consists of maximal safe resection, followed by craniospinal radiation (in patients 3 years and older) and adjuvant chemotherapy. Advances in clinical stratification of this tumor have allowed establishment of treatment de‐escalation trials aimed at reducing long‐term side effects. However, there have been few advances in identifying novel therapeutic strategies for MB patients due to difficulties in creating chemotherapeutics that can bypass the blood‐brain‐barrier—among other factors. On the other hand, with the help of whole genome sequencing technologies, molecular pathways involved in MB pathogenesis have become clearer and have helped drive MB research. Regardless, this advance in research has yet to translate to the clinic, which may be due to the inability of current in vivo and in vitro models to accurately recapitulate this heterogeneous tumor in humans. Conclusions: There have been significant advances in knowledge and treatment of medulloblastoma over the last few decades. Whole genome sequencing has helped elucidate clear differences between the subgroups of MB, allowing physicians to better tailor treatments to each patient in an effort to reduce long‐term sequelae. However, there are still many more obstacles to overcome, including less cytotoxic therapies in the clinic and better modeling systems to accurately replicate this disease in the laboratory. Scientists and physicians must work in a more cohesive manner to create translatable results from the laboratory to the clinic—helping improve therapies for medulloblastoma patients.